Karyotype analysis of some species of Hyoscyamus and Archihyoscyamus genera (Solanaceae) from Turkey - Dogan, Gulden; Kaplan, Zulfiye Kazez; Kiran, Yasar (Univ Tokyo Cytologia, 2025)
This study investigated the somatic chromosome numbers and morphometric properties of five species belonging to the genera Hyoscyamus and Archihyoscyamus (Solanaceae) from Turkey. These species are H. albus L., H. aureus L., H. niger L., H. reticulatus L., and A. leptocalyx (Stapf) A.M.Lu. The chromosome number and morphology of the species were investigated using karyological techniques. In the literature, two different basic chromosome numbers are mentioned for the Hyoscyamus genus, x= 14 and 17. However, the chromosome number was determined as 2n=2x= 34 in all species used in this study. The Stebbins classification system grouped all species in class 2A. Also, chromosome number, total chromosome length, haploid chromosome length, relative length, arm ratio, centromere index, centromere position, karyotype asymmetry values, and karyotype formula were determined. Chromosome numbers of H. aureus and A. leptocalyx were defined for the first time in this study.
Keywords: Archihyoscyamus; Hyoscyamus; Chromosome number; Karyotype; Solanaceae; Turkey